Wirsung Septectomy - Armand Ugón, Alfredo; Estefan, Alberto; Lago, Fernando; Pacheco, Héctor (Cirugía del Uruguay, 1986)
Presenting four observations of a septectomy of the inter-wirsung-choledoclan wall. Stressed is the importance of obstruction of Wlrsung's duct in bllio-pancreatic affections and difficulties to arrive to a correct diagnosis in this field.